Cyber-Crime in India and Necessary Reforms in the Present Legal System: Addressing the Challenges of Cyber-Crime in India (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Law is needed to prevent any crime, if there is a deficiency in the law itself then justice will not be able to achieve its purpose and if the law is fair and right but there is a lack in the institutions that implement it, then the results will not be achieved. Crimes which keep on changing according to the time, the need for necessary changes in laws and institutions is needed from time to time, such as Cyber-crime which is currently a serious problem for the country, necessary changes in the laws crime and institutions accordingly. Changes have become an absolute necessity at present.